Are some meteoroids rubble piles?. Issue Volume 10:Issue S318(2015) (1st March 2016) - Borovička, Jiří
Abstract: The possibility that some meteoroids in the size range 1 – 20 meters are rubble piles i.e. assembles of boulders of various sizes held together only by small van der Waals forces, is investigated. Such meteoroids are expected to start disrupting into individual pieces during the atmospheric entry at very low dynamic pressures of 25 Pa, even before the onset of ablation. The heterogeneous bodies as Almahata Sitta (asteroid 2008 TC3 ) and Benešov are primary candidates for rubble piles. Nevertheless, by analyzing the deceleration, wake, and light curve of the Benešov bolide, we found that the meteoroid disruption started only at a height of 70 km under dynamic pressure of 50 kPa. No evidence for a very early fragmentation was found also for the Chelyabinsk event.